2021
DOI: 10.1186/s11671-021-03595-y
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Atomic and Electronic Structure of Stacked-Cup Carbon Nanofibers

Abstract: We report results of comprehensive experimental exploration (X-ray photoemission, Raman and optical spectroscopy) of carbon nanofibers (CNFs) in combination with first-principles modeling. Core-level spectra demonstrate prevalence of sp2 hybridization of carbon atoms in CNF with a trace amount of carbon–oxygen bonds. The density functional theory (DFT)-based calculations demonstrated no visible difference between mono- and bilayers because σ-orbitals are related to in-plane covalent bonds. The influence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In another study [281], the C 1s high-resolution core line revealed neglectable heteroatoms (O/C ratio is 0.019), confirming the purity of the sp 2 graphitic phases in the CNF. Optical measurements exhibit an absorption peak located in the UV region at 270 nm, while the emission spectra display a peak at 420 nm.…”
Section: Carbon Nanofibersmentioning
confidence: 83%
“…In another study [281], the C 1s high-resolution core line revealed neglectable heteroatoms (O/C ratio is 0.019), confirming the purity of the sp 2 graphitic phases in the CNF. Optical measurements exhibit an absorption peak located in the UV region at 270 nm, while the emission spectra display a peak at 420 nm.…”
Section: Carbon Nanofibersmentioning
confidence: 83%